Determinants of Overseas Filipino Worker (OFW) remittances - Renato E. Reside (University of the Philippines, School of Economics (UPSE), 2009)
This study estimates determinants of remittances to the Philippines. Remittance growth responds to real growth in the Philippines and in host countries, exchange rates, interest and deployment rates, inflation, as well as to immigration and employment policies. While most studies conclude that remittances are exclusively either driven by altruistic or self-interested motives, the evidence in this study supports remittances driven by both. The dual nature of remittances means that remittances can contribute to both consumption smoothing and business cycle amplification. Thus, remittances can be either countercyclical or procyclical depending on the shocks affecting them. Nominal price and exchange rate shocks give rise to the former response, while real shocks lead to the latter response.
Keywords: 330; Rücküberweisungen; Arbeitsmigranten; Beschäftigungseffekt; Wirtschaftswachstum; Philippinen